Synthesis of New Series Bis-3-Chloro-β-Lactam Derivatives from Symmetrical Bis-Schiff Bases as Effective Antimicrobial Agents with Molecular Docking Studies - Hassan, Sangar A.; Abdullah, Media N.; Aziz, Dara M. (Science Journal of University of Zakho, 2021)
Endeavoring to find a new type of antimicrobial agents, a new sequence of bis-Schiff bases and bis-3-cholro-β-lactams are synthesized. An astonishing class of strained compounds is part of the symmetrical bis-Schiff bases that has widespread applications and building blocks for the combination of bis-3-cholro-β-lactams antibiotics. Bis-3-cholro-β-lactams are synthesized through (Staudinger) [2+2] ketene-imine cycloaddition reaction. Structures of the produced compounds are deduced by 1H, 13C-NMR, and FT-IR spectroscopies. All produced compounds are shown moderate to good antimicrobial activity compared to human pathogenic bacteria strains (Escherichia coli and Staphylococcus aureus), also compared to Aspergillus Niger and Trichophyton mentagrophytes fungi through the broth microdilution technique. A molecular docking study is used for showing the active sides and binding affinity of the products with the target proteins or receptors of E. coli (PDB ID: 3GI9).